Analysis of Misconceptions among Physics Education Students on Special Relativity Theory - Ana Dhiqfaini Sultan; Dewi Hikmah Marisda; Yusri Handayani; Ma'ruf Ma'ruf (Unversitas Muhammadiyah Mataram, 2025)
This study explores persistent misconceptions among students in physics education programs regarding the Special Theory of Relativity. Despite formal instruction, many still show fragmented understanding, often reverting to classical concepts. The aim is to identify dominant misconceptions and analyze cognitive and pedagogical causes. Using a qualitative descriptive method, 25 fifth-semester physics education students from a public university in Indonesia participated. Data were collected through a validated 20-item multiple-choice diagnostic test and semi-structured interviews. Analysis involved data reduction, narrative development, and expert triangulation. Results show frequent misconceptions in time dilation (72%), length contraction (64%), and simultaneity (60%). Students misinterpret time dilation as an absolute change, view length contraction as permanent, and fail to understand simultaneity’s relativity. Contributing factors include limited visual aids, inadequate contextual teaching, and lack of engaging media. To address this, the study suggests using digital tools like simulations and animations and adopting constructivist-based strategies. These are expected to deepen understanding and correct misconceptions. The findings aim to enhance modern physics teaching at the tertiary level.